Well-differentiated liposarcoma causing non-islet cell tumor hypoglycemia - Igarashi, Yosuke; Hirukawa, Hiroshi; Nakano, Tetsuya; Morimoto, Yuta; Fukuda, Shintaro; Tada, Tetsuya (International cancer conference journal, 2022)
Non-islet cell tumor hypoglycemia (NICTH) is a paraneoplastic syndrome that causes severe hypoglycemia. The tumor involved produces high-molecular-weight insulin-like growth factor-II (IGF-II). NICTH can be caused by various benign and malignant tumors. However, NICTH due to liposarcoma (LPS) is rare. A 38-year-old man was brought to the hospital emergency department with complaints of vomiting and unconsciousness. His abdomen was distended, and a large tumor was palpable. He had severe hypoglycemia that required continuous glucose infusion. Radiological examination revealed a large 40-cm mass that filled the abdominal cavity, and LPS of the mesentery was suspected. Laboratory data showed low levels of insulin, C-peptide, and IGF-I concentrations. Subsequently, an LPS-induced NICTH was suspected. Complete resection of the tumor and the encased small intestine was performed. The pathological diagnosis was well-differentiated liposarcoma (WDLPS). The Western immunoblot showed that the high-molecular-weight IGF-II confirmed in the serum preoperatively, had almost disappeared postoperatively. Based on these findings, NICTH caused by a WDLPS was diagnosed. The postoperative course was uneventful. In the last 4 years since the primary operation, the patient had not experienced further hypoglycemia symptoms. Here, we report a case of NICTH caused by a large WDLPS. NICTH should be considered in patients with both severe hypoglycemia and large tumors. In these cases, appropriate treatment including semi-urgent surgery should be provided.